2023
DOI: 10.1002/pro.4734
|View full text |Cite
|
Sign up to set email alerts
|

Role and structure of the small subunit forming heterodimers with laccase‐like enzymes

Abstract: Unlike laccases sensu stricto, which are usually monomeric enzymes, laccase‐like enzymes recently re‐classified as Novel Laccases (NLACs) are characterized by the formation of heterodimers with small proteins (subunits) of unknown function. Here the NLAC from Pleurotus eryngii (PeNL) and a small protein selected from the fungal genome, that is homologous to reported POXA3 from Pleurotus ostreatus, were produced in Aspergillus oryzae separately or together. The two proteins interacted regardless of whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Moreover, the crystal structure of a small subunit was solved for the first time. Finally, the observed interactions between the catalytic and the small subunit indicated that the NLAC holds structural features likely involved in substrate binding and/or the interaction with the small subunit, which could explain the differences in activity and stability of monomeric or complexed NLACs, as well as of NLACs compared to laccases sensu stricto [77].…”
Section: Laccase-ferroxidases (Lac-foxs)mentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the crystal structure of a small subunit was solved for the first time. Finally, the observed interactions between the catalytic and the small subunit indicated that the NLAC holds structural features likely involved in substrate binding and/or the interaction with the small subunit, which could explain the differences in activity and stability of monomeric or complexed NLACs, as well as of NLACs compared to laccases sensu stricto [77].…”
Section: Laccase-ferroxidases (Lac-foxs)mentioning
confidence: 97%
“…This has been recently confirmed during the expression and characterization of the heterodimeric complex formed by the NLAC of P. eryngii with a small protein identified in the genome of the fungus. In that study, the stability to pH, temperature and presence of organic co-solvents and the catalytic activity of the enzyme was remarkably increased by the presence of the small subunit [77]. Moreover, the crystal structure of a small subunit was solved for the first time.…”
Section: Laccase-ferroxidases (Lac-foxs)mentioning
confidence: 98%